Dynamic characteristics and fatigue life analysis of the gyration platform of roadheader. - Shan Gao; Zhen Tian; Wei Liu; Lijuan Zhao; Yang Ge; Quan Sun (PLoS ONE)
In order to investigate the dynamic characteristics and fatigue life of the roadheader's gyration platform during the cutting process, the calculation of the cutting head load was achieved based on the force and its transformation of cutting pick, and the transient loads in the two lateral swing directions of the roadheader were calculated. Subsequently, the simulated load was applied to the multi-body model of the cutting section, and dynamic simulations were conducted. Critical information, including stress and strain distribution, as well as the maximum stress on the gyration platform, was extracted from these simulations. The study reveals that during the left-to-right cutting of the rock, the gyration platform experiences significant stress, with the high dynamic stress focus primarily concentrated at the bolt holes connected to the rotary bearings. Deformation was predominantly observed on both sides of the lifting cylinder and the rear portion of the gyration platform. Furthermore, both the maximum stress and deformation of the gyration platform exhibit a noticeable increasing trend with the escalation of swing speed. The correlation established indicates that elevated swing speeds lead to heightened dynamic stress on the gyration platform, consequently causing a noteworthy decrease in its fatigue life. To ensure the reliability of the gyration platform, it is crucial to judiciously select the swing speed based on the hardness of the rock, especially when cutting in different swing directions. The research results have important reference value for improving the structure and performance of the gyration platform.